Non-invasive ventilation in acute respiratory failure in children - Clara Abadesso; Pedro Nunes; Catarina Silvestre; Ester Matias; Helena Loureiro; Helena Almeida (MDPI AG, 2012)
The aim of this paper is to assess the clinical efficacy of non-invasive ventilation (NIV) in avoiding endotracheal intubation (ETI), to demonstrate clinical and gasometric improvement and to identify predictive risk factors associated with NIV failure. An observational prospective clinical study was carried out. Included Patients with acute respiratory disease (ARD) treated with NIV, from November 2006 to January 2010 in a Pediatric Intensive Care Unit (PICU). NIV was used in 151 patients with acute respiratory failure (ARF). Patients were divided in two groups: NIV success and NIV failure, if ETI was required. Mean age was 7.2±20.3 months (median: 1 min: 0,3 max.: 156). Main diagnoses were bronchiolitis in 102 (67.5%), and pneumonia in 44 (29%) patients. There was a significant improvement in respiratory rate (RR), heart rate (HR), pH, and pCO2 at 2, 6, 12 and 24 hours after NIV onset (P<0.05) in both groups. Improvement in pulse oximetric saturation/ fraction of inspired oxygen (SpO2/FiO2) was verified at 2, 4, 6, 12 and 24 hours after NIV onset in the success group (P<0.001). In the failure group, significant SpO2/FiO2 improvement was only observed in the first 4 hours. NIV failure occurred in 34 patients (22.5%). Risk factors for NIV failure were apnea, prematurity, pneumonia, and bacterial co-infection (P<0.05). Independent risk factors for NIV failure were apneia (P<0.001; odds ratio 15.8; 95% confidence interval: 3.42-71.4) and pneumonia (P<0.001, odds ratio 31.25; 95% confidence interval: 8.33-111.11). There were no major complications related with NIV. In conclusion this study demonstrates the efficacy of NIV as a form of respiratory support for children and infants with ARF, preventing clinical deterioration and avoiding ETI in most of the patients. Risk factors for failure were related with immaturity and severe infection.